2023
DOI: 10.3389/fbioe.2023.1103611
|View full text |Cite
|
Sign up to set email alerts
|

ROS-scavenging hydrogel as protective carrier to regulate stem cells activity and promote osteointegration of 3D printed porous titanium prosthesis in osteoporosis

Abstract: Stem cell-based therapy has drawn attention as an alternative option for promoting prosthetic osteointegration in osteoporosis by virtue of its unique characteristics. However, estrogen deficiency is the main mechanism of postmenopausal osteoporosis. Estrogen, as an effective antioxidant, deficienncy also results in the accumulation of reactive oxygen species (ROS) in the body, affecting the osteogenic differentiation of stem cells and the bone formation i osteoporosis. In this study, we prepared a ROS-scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…Recent researchers have observed that stem cells cultured with more hydrophilic materials in a 3D environment could reduce differentiation. They found that hydrophobic materials produced excessive levels of reactive oxygen species (ROS), which can trigger cell differentiation [64,65]. Based on this view, Bai et al [66] fabricated a zwitterionic poly(carboxybetaine)based hydrogel (ZTG) using a specifically selected metalloproteinase-cleavable zwitterionic peptide to reversibly crosslink the gels.…”
Section: Stem Cell Expansionmentioning
confidence: 99%
“…Recent researchers have observed that stem cells cultured with more hydrophilic materials in a 3D environment could reduce differentiation. They found that hydrophobic materials produced excessive levels of reactive oxygen species (ROS), which can trigger cell differentiation [64,65]. Based on this view, Bai et al [66] fabricated a zwitterionic poly(carboxybetaine)based hydrogel (ZTG) using a specifically selected metalloproteinase-cleavable zwitterionic peptide to reversibly crosslink the gels.…”
Section: Stem Cell Expansionmentioning
confidence: 99%
“…Ding et al developed a ROS-scavenging hydrogel by crosslinking EGCG, 3-acrylamido phenylboronic acid and acrylamide, and encapsulated bone marrow MSCs within it. The hydrogel effectively enhanced osteointegration of 3D-printed microporous titanium alloy prostheses in an osteoporotic rabbit model, exhibiting the ability to scavenge accumulated ROS, suppress inflammatory cytokine expression and improve osteogenesis-associated markers [219]. Melatonin has been shown to possess free-radical scavenging and antioxidant properties, complementing its crucial role in bone formation [220].…”
Section: Bone Diseasesmentioning
confidence: 99%
“…Under normal physiological conditions, ROS produced by OCs stimulate and promote bone tissue absorption (48). However, deficiency of the potent antioxidant estrogen leads to the accumulation of ROS in the body which in turn affects osteogenic differentiation of stem cells and the formation of osteoporosis (49).…”
Section: Rank/rankl/opg Pathwaymentioning
confidence: 99%